Effect of capital adequacy, credit risk, and operational efficiency on profitability with liquidity as an intervening variable for BUMN Banks 2018-2022 - Muknin Aji Setiawan; Habibah Sulaiman Fauziyyah; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2022)
This study aims to determine Capital Adequacy Ratio (CAR), Non Performing Loans (NPL) and Operational Efficiency (BOPO) to Profitability (ROA) with Loan to deposit Ratio (LDR) as Intervening Variables in BUMN Banks in 2018-2022. The research method used is a quantitative method with a sample of 4 state-owned banks. The data used is secondary data in the form of panel data taken from annual reports published on the website of the IDX (Indonesian Stock Exchange) which are analyzed using the sobel test analysis technique. Data were analyzed using the eviews 9 program. The conclusion from the results of this study was that CAR had a negative and significant effect on LDR, NPL and BOPO had no significant effect on LDR, CAR and BOPO had a negative and significant effect on profitability, NPL had no significant effect on profitability, LDR had an effect positive and significant effect on profitability. LDR can mediate the effect of CAR on Profitability, LDR cannot mediate the effect of NPL and BOPO on Profitability.